Development of Interactive Powerpoint Learning Media to Improve Students' Understanding of Mathematical Concepts Statistics in Class VIII - Haryati, Mega; Ramdhani, Lisda; Rahmawan, Ardi (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research aims to determine the development of interactive Powerpoint learning media to improve students' understanding of mathematical concepts in class VIII statistics material. This type of research is quantitative descriptive research using R&D using the ADDIE model. Subjects were 8 respondents by random sampling. The research instrument is a questionnaire using a Likert scale. Results obtained At the development stage using 3 experts, the results were 87.5% for media experts, 100% for material experts and 90.6% for language experts regarding student concept understanding with an average of 92.7%. The Implementation stage ; 1) The media is easy to use total score of 29 and a percentage of 91% in the Very Appropriate category, 2) The language used is easy to understand total score of 30 and 94% in the Very Appropriate category, 3) Image suitability as many as total score of 29 and 91% in the Very Appropriate category, 4) Interest S Suitability of Images total score of 31 and 97% in the Very Appropriate category, and 5) Understanding the Concept Well total score of 30 and 95% in the Very Eligible category. The overall average is 93.1% with a very decent category.